Effect of the Amount of Carbon in the Fe3O4@ZnO-C Nanocomposites on Its Structure and Magnetic Properties - Astuti Astuti; Syukri Arief; Devi Pebrina (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2022)
Synthesis and characterization of structure magnetic properties of Fe3O4@ZnO- C nanocomposite have been done through the precipitation method. This study aimed to discover the effect of concentrations/thickness of carbon layer on crystal structure and magnetic properties of Fe3O4@ZnO-C nanocomposites. Fe3O4 and Fe3O4@ZnO were the samples used in the study, and variations in the amount of carbon were 0.2, 0.1, and 0.05 g. Nanocomposites were characterized using X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), and vibrating sample magnetometer (VSM). Based on the results of XRD, it has been found that the crystal structure for Fe3O4 was cubic, while ZnO was hexagonal wurtzite. The addition of carbons to Fe3O4@ZnO caused a broadening of the diffraction peaks and a decrease in the degree of crystallinity. The bonds formed on Fe3O4@ZnO-C nanocomposites, i.e. Fe-O bonds indicated the formation of Fe3O4, Zn-O bonds showed the formation of ZnO and C-O, C-H, and O-H bonds revealed the presence of a carbon layer originated from glucose. The VSM results showed that the magnetic saturation decreased with increasing carbon mass. Overall, the carbon-coated nanocomposite material with a carbon mass variation of 0.2, 0.1, and 0.05 g showed superparamagnetic properties with a magnetic saturation of 18.23 emu/g, 19.33 emu/g and 22.05 emu/g, while for the coercive field of 92.29 Oe, 92.90 Oe and 89.60 Oe, respectively. Based on these characterization results, Fe3O4@ZnO-C nanocomposite materials can potentially be developed as biomedical materials, such as the materials for photothermal therapy for cancer cells.